Two notes on Aristotle and Aristarchus on the meaning of κέρας in the Iliad - Mayhew, Robert (Hyperboreus, 2016)
This essay examines two sets of texts, each of which describes how Aristotle and Aristarchus interpreted κέρας (‘horn’) in the Iliad (in verses 11. 385 and 24. 81). In addition to providing a better understanding of these texts, the essay attempts to show that (1) scholars have been too quick to emend Ἀριστοτέλης to Ἀρίσταρχος, and (2) that four of the texts discussed are neglected source-texts for Aristotle’s lost Homeric Puzzles, which ought to be included in any subsequent collection of the fragments of Aristotle.